Conservation Technology and Capital Formation In Arid Agriculture - Jodha, N S (Annals of Arid Zone, 2016)
In the ill-watered areas modern. conservation ,technology, embodied in different resource conservation measures, can offer some solution to the principal problems of low and unstable farm production and fast depletion of resource base. Some of the conservation measures being permanent land improvements, constitute part of farm capital. ,Thus increased capital formation in terms of conservation .measures can ensure quicker spread. of conservation technology in arid agriculture. But, these conservation measures’ find insignificant place in the existing structure of farm capital in the arid region. Their share in plan expenditure (19.56.-5.7 to 19.6-7- 8) wasÂ· only 2.57 per cent of the total. In.91ost of the districts surveyed by the Reserve Bank of India and others,’ conservation measures accounted for less than 2 per cent of the total capital formation by private farmers. Increased capital formation (maintaining its. present structure, t e. predominance of livestock and farm implements and complete neglect or conservation measures may have several undesirable implications. It can accentuate the process of resource depletion. without ensuring development of arid agriculture. The situation calls for a change.